Effect of abscisic acid on rice yield quality (Oryza sativa L) in three locations of northeastern Peru (Bioagro, 2026)
Rice is a crop of great economic importance nationally; however, yields have remained stable in recent years, even under intensive management systems. In this context, abscisic acid has shown favorable effects on grain filling regulation and improved crop yield efficiency. The objective of this study was to evaluate its effect on rice yield and quality in three locations in the Rioja province, San Martín region, Peru. Three doses (0, 30, and 60 g·ha⁻¹) of the commercial product InGrain™ (20% S-abscisic acid) were used in a completely randomized block design at each location with three replicates. A combined analysis was subsequently performed with the environment as a fixed factor, evaluating the effects of dose, environment and their interaction. The 60 g·ha⁻¹ dose significantly increased yield in Yuracyacu (12,135.00 kg·ha⁻¹; +14%) and Rioja (11,723.33 kg·ha⁻¹; +19%), in addition to reducing empty grains by 38% in the latter location. It also increased pile yield by 2 % and the percentage of whole grains by 5 %. The variation between locations demonstrated the influence of the environment on the magnitude of the effect, highlighting the importance of the genotype-by-environment interaction in productive expression. It is concluded that abscisic acid can improve crop performance under field conditions, although its effectiveness depends on local agroclimatic conditions.
Keywords: Genotype environment interaction; grain filling; hormones; milling yield